An annotated catalogue of the New World Therevidae (Insecta: Diptera: Asiloidea) - Webb, Donald W.; Gaimari, Stephen D.; Hauser, Martin; Holston, Kevin C.; Metz, Mark A.; Irwin, Michael E.; Kampmeier, Gail E.; Algmin, Kristin (Zootaxa, 2013)
The genera and species of New World stiletto flies (Diptera: Therevidae) are listed, with annotated references to nomenclature, synonymies and generic combinations, type localities, the primary type depositories, distribution, and citations for the most recent revisions. The genus Cyclotelus Walker, 1850 (along with its synonyms Furcifera Kröber, 1911, and Epomyia Cole, 1923a) is synonymized under Cerocatus Rondani, 1848. Ectinorhynchus fascipennis Kröber, 1911 is given the new name Cerocatus rondanii Gaimari, and Phycus rufiventris Kröber, 1911 is given the new name Cerocatus raspii Hauser. Phycus analis Kröber, 1911 and Phycus bicolor Kröber, 1911, are placed as new combinations in Cerocatus Rondani, as are the following species that were previously in combination with Cyclotelus: Furcifera achaeta Malloch, 1932, Cyclotelus badicrusus Irwin and Webb, 1992, Phycus beckeri Kröber, 1911, Epomyia bella Cole, 1923a, Furcifera braziliana Cole, 1960a, Cyclotelus colei Irwin and Lyneborg, 1981a, Thereva diversipes Kröber, 1911, Thereva fascipennis Macquart, 1846a, Psilocephala femorata Kröber, 1911, Furcifera flavipes Kröber, 1928b, Furcifera hardyi Cole, 1960a, Furcifera kroeberi Cole, 1960a, Cyclotelus laetus Walker, 1850, Furcifera longicornis Kröber, 1911, Cyclotelus nigroflammus Walker, 1850, Psilocephala nigrifrons Kröber, 1914a, Thereva pictipennis Wiedemann, 1821, Furcifera polita Kröber, 1911, Cyclotelus pruinosus Walker, 1850, Thereva ruficornis Macquart, 1841a, Psilocephala rufiventris Loew, 1869, Thereva scutellaris Walker, 1857, Cyclotelus silacrusus Irwin and Webb, 1992, Cyclotelus socius Walker, 1850 and Psilocephala sumichrasti Bellardi, 1861. Dialineura pallidiventris Malloch, 1932, Melanothereva blackmani Oldroyd, 1968, Thereva maculicornis Jaennicke, 1867 and Thereva notabilis Macquart, 1841a are placed as new combinations in Entesia Oldroyd. Henicomyia amazonica Irwin and Webb, 1992 is a new synonym of Henicomyia flava Lyneborg, 1972. Henicomyia varipes Kröber, 1912a is given revised species status from former synonymy withHenicomyia hubbardii Coquillett, 1898.